Neurosains Dalam Mengembangkan Kecerdasan Intelektual Peserta Didik Sd Islam Al-Azhar Bumi Serpong Damai - Susanto Susanto; Ida Royani Munfarohah (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2020)
Neuroscience in developing intellectual intelligence is crucial to known by all teachers. Because, nervous system structure is underlying human action in terms of cognitive, affective, and pshycomotoric. So, teachers easier in developing intelligence by using fun and interesting learning method. This research purpose is to know and to search information related to neuroscience in developing students’ intellectual intelligence at Al-Azhar Islamic Elementary School Bumi Serpong Damai. This research type is descriptive qualitative by using phenomenology method. To reach this purpose researcher has interviewed five teachers as core informant and one principal as supporting informant. Moreover, researcher also observed and study documents. The research result show that neuroscience can be developing students’ intellectual intelligence at Al-Azhar Islamic Elementary School Bumi Serong Damai. This matter indicated by students are more enthusiastic in learning, active in asking, think more divergent, and also higher learning motivation during learning process. So, students be able to learn without coercion, earnestly and learning process occur with pleasure